2013
DOI: 10.1016/j.chemosphere.2013.01.109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polyurethane foam and XAD-2 sampling matrices to measure airborne organophosphorus pesticides and their oxygen analogs in an agricultural community

Abstract: Side-by-side active air sampling for the organophosphorus (OP) pesticide, chlorpyrifos (CPF) and its oxygen analog, chlorpyrifos-oxon (CPF-O) was conducted with two recommended air sampling matrices: OSHA Versatile Sampling (OVS) tubes with XAD-2 resin, polyurethane foam (PUF) tubes, and passive PUF deposition disks. The study compared the proportion of artificially transformed CPF-O in the laboratory and in the field during a tree fruit application in Washington State. Lab results demonstrated that the NIOSH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…In the 2009 study, CPF, AZM, and their oxygen analogs were identified in the outdoor air of the surrounding agricultural communities, indicating direct atmospheric transformation. Other studies have also reported these compounds in air ( Armstrong et al 2013b ; CARB 1998 ; CDPR 2006 , 2009 ).…”
Section: Introductionmentioning
confidence: 83%
“…In the 2009 study, CPF, AZM, and their oxygen analogs were identified in the outdoor air of the surrounding agricultural communities, indicating direct atmospheric transformation. Other studies have also reported these compounds in air ( Armstrong et al 2013b ; CARB 1998 ; CDPR 2006 , 2009 ).…”
Section: Introductionmentioning
confidence: 83%
“…27,190 There is indeed evidence that transformation of chlorpyrifos into its oxon-analog can occur when air is pulled through XAD-2 resin. 260 When exposing parent PAHs and alkylated PAHs spiked onto PUF-disks to ozone levels equivalent to two months of deployment in a ow tube, many compounds showed signicant reactive loss, especially at low relative humidity. 261 When comparing the amounts of SVOCs sequestered in four PUF-PASs deployed for four consecutive weekly periods with those in a PUF-PAS deployed simultaneously for one full month, much higher levels of several PAHs, PBDEs and other BFRs in the PASs deployed for shorter periods were taken as an indication that those substances were degraded during the longer sampling period.…”
Section: F2 Explanations Of the Variability In Empirically Determinementioning
confidence: 99%
“…For example, it was recently reported that XAD-2 'articially transformed' chlorpyrifos to its oxygenated analogue chlorpyrifos-oxon to a substantial extent whereas PUF used in the same study did not. 32 Because pendimethalin and triuralin have a similar dinitro-aniline structure, they both may be prone to the same type of reaction process(es). Additional studies are required to explore this hypothesis experimentally; PAS-SIM model simulations incorporating this process are presented below.…”
Section: Pesticide Monitoring By Xad-pas and Lv-aasmentioning
confidence: 99%